DYNAMIC ANALYSIS OF TBM DRIVING SYSTEM IN UNCERTAIN GEOLOGY - ZHU QingDong (Jixie qiangdu)
In order to study the difference of vibration response of TBM driving system under uncertain geology and how to select reasonable driving forms according to different geological conditions,a dynamic analysis method of TBM driving system in uncertain geology is proposed. Firstly,a geological equivalent model and typical working condition model are established,and a multi-degree-of-freedom coupled dynamic model of TBM driving system is established by the lumped mass method. Then,according to different geological conditions and combined with interval theory,the interval loads of each working conditions corresponding to geological conditions are obtained,and the interval loads are substituted into the dynamic model to obtain the dynamic response of various driving modes under uncertain geology and working conditions. Finally,by comparing the dynamic response intervals of different driving modes under maximum thrust conditions,the results are as follows:（ 1） When the geology of TBM tunneling is complex rock strata,the driving form of symmetrical distribution is relatively stable.（ 2） When the geology is homogeneous strata,the uniform distribution is stable.（ 3） With the increase of the number of hard rock in geology,the influence of the layout of driving system on vibration is gradually increasing.